Implementation of Double Fortified Salt in India is based on Low Scientific Evidence - Kapil, Umesh; Sareen, Neha (Indian Journal of Community Health, 2014)
Micronutrient malnutrition (MNM) can affect all age groups, but young children and women of reproductive age are most at risk of developing micronutrient deficiencies. Iodine Deficiency Disorders (IDD) and Iron Deficiency Anaemia (IDA) are two important Public Health problems. Out of 342 districts surveyed, so far IDD is a major public health problem in 286 districts. No state in India is free from iodine deficiency (1). Iron Deficiency Anaemia is reported in about 70% of the population across all age groups (2). The magnitude of Vitamin B12 deficiency is documented to be about 73.5% in the adolescents (3) and Zinc deficiency is reported in about 49.4% amongst children (4). In addition, there are deficiencies of other micronutrients and minerals like Folic Acid, Vitamin D which are of public health concern. Fortification of food is one of three primary strategies to combat micronutrient deficiencies. Fortification is defined by the World Health Organization (WHO) and Food and Agricultural Organization (FAO) as "the practice of deliberately increasing the content of an essential micronutrient, i.e. Vitamins and minerals (including trace elements) in a food irrespective of whether the nutrients were originally present in the food before processing or not, so as to improve the nutritional quality of the food supply and to provide a public health benefit with minimal risk to health”. Food fortification is one of the most cost effective ways to make up for the deficient vitamins and minerals in low quality diets. The edible salt is the most widely used food vehicle for fortification with micronutrients (5). Fortification of salt with iodine, to prevent IDD, under the National Iodine Deficiency Disorders Control Programme, is in operation since 1962 (1). This intervention has led to significant prevention and control of IDD (6). Recently, the technology has been developed for fortification of salt with iron and iodine commonly known as DFS, to simultaneously combat IDD and IDA (7-9).